Feasibility, acceptability and safety of a nurse led hepatitis B clinic based in the community. Issue 2 (June 2015) - Pritchard-Jones, Janice; Stevens, Catherine; McCaughan, Geoffrey; Strasser, Simone
Summary Aim The aim of this study was to investigate if a community based hepatitis B (HBV) nurse clinic is a feasible, acceptable and safe strategy to improve access to best practice chronic hepatitis B care (CHB) in Sydney Local Health District. Methods The weekly clinic commenced in an Inner West Sydney Health Centre in November 2012. The CNC responsibilities included patient assessment, management, education, triage, the development of care plans for GPs and GP support. Nursing practice was guided by recommendations from internationally and nationally endorsed CHB Guidelines. Information on patient demographics, clinical findings, triage decisions and sources of referral were collected and used to assess the feasibility, acceptability and safety of the nurse clinic. Patients were also invited to complete a self-administered survey. The survey included questions on attitudes towards the clinic and opinions on barriers to accessing treatment and care. Data was collated and analysed in both Excel and SPPS. Results In the first 18 months of the clinic 66 people attended, 56 (80%) had CHB, 51 (77%) were born in an Asian country. An equal number of males and females attended. 11 (17%) required further management at a hospital based liver clinic and were referred. 5 (8%) have commenced anti-viral treatment. 24 (36%) met the criteria for six monthly HCC screening and were commenced on HCC surveillance. Twenty-two GPs referred patients. 11 (17%) patients returned the survey and they reported a high level of satisfaction with the clinic and willingness to engage in future CHB care. Conclusions This study of a community based CHB nurse clinic shows it is a feasible, acceptable, and safe initiative. The nurse improved access to best practice care and supported patients to effectively manage their CHB. We have confirmed a nurse can have a central role in triage, case management and GP support. Given the high CHB prevalence in our LHD a higher number of GP referrals were expected. Further research on how to increase engagement with GPs and people living with CHB is needed. We plan to expand our model with the CHB nurse conducting assessments and education in GP practices.